Exploring the perspectives of cross-cultural instructors on integrating 21st century skills into EFL university courses - Alharbi, Noof Saleh (Frontiers in Education, 2024)
Integrating 21st century skills, including communication, collaboration, problem-solving, and critical thinking, into English as a Foreign Language (EFL) university courses is imperative. This study adopts a tripartite focus: (1) investigating cross-cultural EFL instructors' perspectives on challenges linked to infusing 21st century skills into Saudi EFL university courses; (2) identifying contributory factors underpinning these challenges; and (3) elucidating proposed strategies for embedding 21st century skills in selected Saudi EFL university classrooms. Using narrative inquiry as a research method, empirical data was garnered through semi-structured interviews involving thirty EFL instructors representing mixed-gender and eight nationalities across multiple Saudi universities. The findings underscore instructors' affirmative disposition towards incorporating 21 st century skills in EFL classes, despite entrenched academic, institutional, collegial, and studentcentered obstacles. Furthermore, the findings spotlight diverse factors exacerbating these challenges, encompassing technological underpinning, temporal constraints, and the absence of robust assessment frameworks, dwindling student engagement, conventional pedagogic paradigms, and administrative complexities. Addressing these challenges necessitates a comprehensive approach characterised by faculty development, curricular realignment, seamless technology integration, collaborative learning ecosystems, student-centric pedagogies, and judicious evaluation mechanisms. Through adopting this holistic approach, educational stakeholders can effectively surmount the intricacies linked with 21st century skill integration, fostering an enriched educational milieu aligned with evolving global imperatives.